Training on Making Desserts from Western Europe in Gerendeng Pulo Village - Etlivia Burianto; Nity Indrawan; Putri Cicilia Jusan (PT. Publikasiku Academic Solution, 2023)
Community Service is a person, group, or institution trying to make a positive contribution to society. Community service is often associated with higher education and research, where students and academics engage in activities that can use their knowledge and skills to help solve problems, improve well-being, and benefit society as a whole. PKM